Consumo de substâncias psicoativas entre mulheres bissexuais e lésbicas: prevalência e associações entre estresse de minorias e apoio social - Sá, Camila Mireli Calaça de (2024)
Drug use among the LGBT population has been a concern for Brazil's comprehensive health policy, health agencies and researchers. However, it is necessary to investigate the conditions under which women from sexual minorities have used psychoactive substances, since internationally there are differences compared to the general population. Thus, this dissertation proposed two studies to investigate this dynamic of use, associated with the Minority Stress Theory and Social Support. To this end, an integrative review of the Brazilian literature on women and substance use in the local reality was carried out. The second study, of a quantitative nature, aimed to analyze how drug use relates to the specific stress experienced by these women and social support. It is discussed that there are different profiles of use and realities mediated by specific experiences, but that minority stress components are associated with use, especially by bisexual women